2022
DOI: 10.1094/pdis-05-21-1115-pdn
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Sclerotinia sclerotiorum Causing Sclerotinia Root Rot on American Ginseng in Northeastern China

Abstract: American ginseng (Panax quinquefolium) is a valuable medicinal plant that is commercially cultivated in China. In May 2020, Sclerotinia root rot of American ginseng was observed on 4-year-old plants in Fusong County in northeastern China, which is the most important part of the country for American ginseng cultivation. The pathogen only infected the tuberous ginseng roots, with sclerotia tightly attached to the root surface. Infected roots, which were brownish and had a watery soft rotted appearance (Fig. 1), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…A rhizosphere microbial community, including soil-borne diseases, plays an important role in determining the health of Panax plants [ 6 , 7 , 8 ]. The pathogens for American ginseng root rot include Fusarium solani , F. oxysporum , and Cylindrocarpon destructans [ 1 , 9 ], which can damage the seedling’s roots, and mainly spread through soil moisture, underground insects, and nematodes [ 10 ]. The previous study on healthy and diseased P. notoginseng showed that the differed composition of bacterial and fungal communities in the rhizosphere soil [ 7 ] and the abundance of Pseudomonas spp.…”
Section: Introductionmentioning
confidence: 99%
“…A rhizosphere microbial community, including soil-borne diseases, plays an important role in determining the health of Panax plants [ 6 , 7 , 8 ]. The pathogens for American ginseng root rot include Fusarium solani , F. oxysporum , and Cylindrocarpon destructans [ 1 , 9 ], which can damage the seedling’s roots, and mainly spread through soil moisture, underground insects, and nematodes [ 10 ]. The previous study on healthy and diseased P. notoginseng showed that the differed composition of bacterial and fungal communities in the rhizosphere soil [ 7 ] and the abundance of Pseudomonas spp.…”
Section: Introductionmentioning
confidence: 99%